2018
DOI: 10.1016/j.jtho.2018.08.1729
|View full text |Cite
|
Sign up to set email alerts
|

P3.04-22 Response of Brain Metastases in Patients with Non-Small Cell Lung Cancer Treated with Immunotherapy and Brain Directed Radiotherapy

Abstract: Background: Immune checkpoint inhibitors (ICIs) targeting PD-(L)1 have shifted the treatment paradigm of advanced non-small cell lung cancer (NSCLC), but responses are often heterogeneous and temporary. Several landmark publications have confirmed the dominant role of gut microbiome in modulating tumor responses to ICIs, suggesting the predictive value of antibiotics (ATB) in patients treated with anti-PD-(L)1 antibody. However, more evidence is needed to comprehensively reveal the association between ATB usag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To improve the prognosis and overcome resistance, some clinical studies have also suggested that PD‐1 and PD‐L1 inhibitors combined with radiotherapy (RT) may be expected to improve the anti‐cancer efficacy. 3 , 4 , 5 Preclinical studies have shown that RT can regulate the immune system, including inducing the abscopal effect, increasing the infiltration and activity of tumor‐related lymphocytes, and elevating the number of tumor neoantigens. 6 The combination of PD‐1/PD‐L1 inhibitors with WBRT/SRS should be evaluated in the era of immunotherapy (IO).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the prognosis and overcome resistance, some clinical studies have also suggested that PD‐1 and PD‐L1 inhibitors combined with radiotherapy (RT) may be expected to improve the anti‐cancer efficacy. 3 , 4 , 5 Preclinical studies have shown that RT can regulate the immune system, including inducing the abscopal effect, increasing the infiltration and activity of tumor‐related lymphocytes, and elevating the number of tumor neoantigens. 6 The combination of PD‐1/PD‐L1 inhibitors with WBRT/SRS should be evaluated in the era of immunotherapy (IO).…”
Section: Introductionmentioning
confidence: 99%